A CORRELATIONAL STUDY BETWEEN LEARNERS’ SATISFACTIONS WITH OFFLINE CLASS AND ENGLISH SELF-EFFICACY DURING THE COVID-19 PANDEMIC - Chris Caesar Pikirang; Nihta Liando; Ceisy N Wuntu (English Education Department, 2021)
Studies described that satisfaction and self-efficacy were mentioned as the utmost influencers in students’ academic performance. By saying that, the study was carried out to expose the level of satisfaction with offline class and English self-efficacy of the students, and to find out is there any correlation between those two-mentioned variables. Through random sample sampling technique, 32 senior high schools students located in local area, Bitung city, were gathered as a sample for this study. Two questionnaire were adapted, first from Asakereh & Dehghannezhad (2015) a questionnaire for satisfaction scale, and second from Sağlam & Arslan (2018) a questionnaire for English self-efficacy. The outcomes revealed that students’ level of satisfaction with offline class and English self-efficacy was at average level. Moreover, a significant negative correlation was revealed between students’ satisfaction with offline class and English self-efficacy. Finally, the study ends with recommendation also suggestion which required to be considered.